2020
DOI: 10.3390/ijerph17217772
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality in Patients with Heart Failure in the Spanish Population: A Cross-Sectional Study

Abstract: Background: Heart failure is a major problem in western societies. Sleep Disorders maintain a bidirectional relationship with heart failure, as shown by studies conducted in other countries. This study aims to describe the quality of sleep in Spanish patients with heart failure. Materials and methods: We carried out a cross-sectional study to analyze the quality of sleep in a sample of 203 patients with a diagnosis of heart failure admitted to an Internal Medicine Service. The Pittsburg Sleep Quality Index (PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
(78 reference statements)
3
8
1
Order By: Relevance
“…All of these factors would be in line with the published evidence, highlighting the percentages of the chronic use of hypnotics, both in the general population at admission with 57% and those who subsequently developed ADE who consumed them daily with 68% [ 7 , 10 , 13 , 34 , 35 , 36 ]. Comparing these data with those of our previous studies carried out in the same unit that applied the drugs in 32.4% of patients hospitalized for COVID-19 [ 23 ], which rose up to 40% among those who developed ADE and 35% relating to HF and sleep quality disorder [ 37 ], a significant increase in the use of these drugs was perceived, whose differences could be found in age, functional, and cognitive impairment.…”
Section: Discussionsupporting
confidence: 61%
“…All of these factors would be in line with the published evidence, highlighting the percentages of the chronic use of hypnotics, both in the general population at admission with 57% and those who subsequently developed ADE who consumed them daily with 68% [ 7 , 10 , 13 , 34 , 35 , 36 ]. Comparing these data with those of our previous studies carried out in the same unit that applied the drugs in 32.4% of patients hospitalized for COVID-19 [ 23 ], which rose up to 40% among those who developed ADE and 35% relating to HF and sleep quality disorder [ 37 ], a significant increase in the use of these drugs was perceived, whose differences could be found in age, functional, and cognitive impairment.…”
Section: Discussionsupporting
confidence: 61%
“…Figure A3 ( Appendix A ), in turn, shows results of APIM research on caregiver quality of life and emotional aspects of dealing with HF patients. Although prior studies indicated similar patterns of relationships [ 55 , 56 , 65 , 66 , 67 , 68 ], an analysis employing the APIM revealed complex interrelationships between patient and caregiver features. Researchers should consider exploring self-care phenomena using the APIM model to analyze the interdependence between the members of the dyad.…”
Section: Discussionmentioning
confidence: 88%
“…Awotidebe et al [ 19 ] reported a significantly worse sleep quality in patients with heart failure compared with healthy controls. In a Spanish study by Jorge-Samitier et al [ 20 ] on a group of 203 patients admitted for decompensated heart failure, poor sleep quality was noted in 73.3%. Javadi et al [ 21 ] revealed poor sleep quality in 91% of hospitalized patients with heart failure.…”
Section: Discussionmentioning
confidence: 99%